The Effect of Online Protests and Firm Responses on Shareholder and Consumer Evaluation - Broek, Tijs van den (Journal of business ethics, 2017)
Protests that target firms’ socially irresponsible behavior are increasingly organized via digital media. This study uses two methods to investigate the effects that online protests and mitigating firm responses have on shareholders’ and consumers’ evaluation. The first method is a financial analysis that includes an event study which measures the effect of online protests on the target firm’s share price, as well as an investigation of the boundary effects of protest characteristics. The second method is an online experiment that assesses the effect of an online protest campaign on consumers’ perception and purchase intention, as well as any mitigating effects that a firm’s response may have. Contrary to recent studies suggesting that participation in online protests is only token support without any substantive effects, our results show that online protests do hurt. Firms can expect to suffer financial, reputational, and sales damage when an online protest campaign mobilizes consumers successfully. We also show that online protests are more likely to take firms by surprise than offline protests. Firms can exacerbate or reduce the damage by their response. We find that although firms may repair the damage to consumers’ purchase intentions, the negative effects on a brand’s image are harder to rectify. The results have valuable implications for protest organizers and managers faced with the task of responding.